2020
DOI: 10.21203/rs.3.rs-78175/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated Serum Total Bile Acid Level at Second Trimester Increases the Risk of Gestational Diabetes Mellitus and Adverse Perinatal Outcomes in Chinese Pregnant Women

Abstract: BackgroudBile acid metabolism is reported to be closely involved in glycolipid metabolism. We investigated the association of the total bile acid (TBA) levels at the second trimester with the risk of gestational diabetes mellitus (GDM) and adverse perinatal outcomes.MethodsWe performed a retrospective cohort study in 2773 Chinese pregnant women. Serum TBA level was measured by a biochemistry automatic analyzer. Logistic regression models with or without restricted cubic splines were performed.Results652 of 277… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…We also found that the number of implantation sites was comparable between the adenomyosis horn and the control horn, suggesting that the presence of adenomyosis not only affects implantation but also affects intrauterine development. These outcomes seem to mimic the high incidence of preterm birth, fetal growth restriction (FGR) and intrauterine fetal death (IUFD).in pregnant women with adenomyosis [9][10][11][12], and this mouse model is expected to be a suitable model of pregnancy complicated by adenomyosis, although further validation is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that the number of implantation sites was comparable between the adenomyosis horn and the control horn, suggesting that the presence of adenomyosis not only affects implantation but also affects intrauterine development. These outcomes seem to mimic the high incidence of preterm birth, fetal growth restriction (FGR) and intrauterine fetal death (IUFD).in pregnant women with adenomyosis [9][10][11][12], and this mouse model is expected to be a suitable model of pregnancy complicated by adenomyosis, although further validation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The number and volume of lesions did not differ between the non-pregnant and postpartum groups.Conclusions: This model can be applied to evaluate the pathogenesis of adenomyosis, validate the e cacy of therapeutic agents, and evaluate the effect of adenomyosis on pregnancy and vice versa.Recently, with the development of noninvasive diagnostic methods such as MRI, adenomyosis can now be diagnosed without a hysterectomy, and it has been revealed that this disease can cause pain, HMB, and infertility [2] [6-8]. Patients with adenomyosis have also been found to have an increased risk of adverse perinatal events such as preterm delivery, fetal growth restriction, and preeclampsia [9][10][11][12]. The…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The number and volume of lesions did not differ between the non-pregnant and postpartum groups.Conclusions: This model can be applied to evaluate the pathogenesis of adenomyosis, validate the e cacy of therapeutic agents, and evaluate the effect of adenomyosis on pregnancy and vice versa.Recently, with the development ofnoninvasive diagnostic methods such as MRI, adenomyosis can now be diagnosed without a hysterectomy, and it has been revealed that this disease can cause pain, HMB, and infertility [2][6-8]. Patients with adenomyosis have also been found to have an increased risk of adverse perinatal events such as preterm delivery, fetal growth restriction, and preeclampsia [9][10][11][12]. The…”
mentioning
confidence: 99%
“…Recently, with the development ofnoninvasive diagnostic methods such as MRI, adenomyosis can now be diagnosed without a hysterectomy, and it has been revealed that this disease can cause pain, HMB, and infertility [2][6-8]. Patients with adenomyosis have also been found to have an increased risk of adverse perinatal events such as preterm delivery, fetal growth restriction, and preeclampsia [9][10][11][12]. The…”
mentioning
confidence: 99%